METHODOLOGICAL APPROACHES TO CLASTER POLICY FORMATION IN AGRARIAN FIELD - Ulyanchenko Y.O. (Pressing Problems of Public Administration, 2015)
In article researched the methodological approaches to the formation of cluster policy in the agrarian sphere. Defined the essence of agricultural clusters, their function and determined the possibility of implementation of cluster policy in the agrarian sphere.